Transparency and Performance of Islamic Banking the Implications for Profit Distribution (Empirical Study of Indonesia and Malaysia) - Indah Setia Utami (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of this paper is to assess the effect of transparency and performance on the distribution of profits in Islamic banks in Indonesia and Malaysia. This study employed content analysis of published annual reports as well as multiple regression analysis. Samples were taken using the purposive sampling technique. The results of the analysis showed that both transparency and performance simultaneously have a positive effect on profit distribution, but partially only transparency has an effect on profit distribution. This could be due to the fact that in Indonesia and Malaysia, Islamic banks operate in a dual banking system where both conventional and Islamic banks coexist. These banks compete with each other for deposit shares.